The Function of E-Commerce in Banggai Regency's Micro, Small, and Medium Enterprises - Rotinsulu, Clara Neltje Meini; Amin, Musdar M; Tandiawan, Vira; Sibay, Yusnita Fitarini (Program Pascasarjana STIE Amkop Makassar, 2023)
In this study, the influence of e-commerce adoption on SMEs in Banggai Regency during the new normal era of Covid-19 was examined. Implementing online shopping, having a strong financial foundation, and maintaining business continuity are the research variables. In the research method, quantitative research is employed, and the reliability of the data, the coefficient of determination, the traditional hypothesis, and the hypothesis are all tested. Implementing the sampling strategy of purposive sampling. 101 participants made up the research sample. The study's findings indicate that financial literacy and e-commerce adoption both significantly improve business continuity. Because the financial literacy of MSME actors significantly affects the sustainability of their firms, the study's findings may have consequences for the government, actors, and potential MSME players. Keywoard: E-Commerce; Literasi; Keuanga; Kelangsungan; Usaha.